Administrative Model Performance of Local Administrative Organizations Udon Thani Province - Phipatviriya, Wanvisa; Saiyasopon, Sukhumvit (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to examine the results of the administrative performance of the authorities in Local administrative organizations, Udon Thani province, 2) to investigate the differences of the administrative performance of the authorities in Local administrative organizations, Udon Thani province, 3) to study the administrative model performance of the authorities in Local administrative organizations, Udon Thani province, and 4) to find out the guidelines for developing the administrative performance in Local administrative organizations, Udon Thani province. The research design used mixed methods. The data analysis included 120 sampling from the authorities and the official administrators of the local administrative organization, Udon Thani. The instruments used in the study was questionnaires. The data were analysed by using frequency, percentage, mean, standard deviations, t-test, and F-test(One Way ANOVA). The findings showed that: 1. The administrative performance results of the authorities in Local administrative organizations in the views of the authorities was in the highest level. 2. Moreover, the differences of the administrative performance of the authorities in Local administrative organizations, Udon Thani province indicated that gender, age, income, and years of experience were overall significantly different at the statistical level of 0.05. On the other hand, the education levels, and the positions was no statistical significance. 3. The administrative model performance of the authorities in Local administrative organizations, Udon Thani province consists of four dimensions which are the performance evaluation, the administration, problems and obstacles of performance, and the follow-up. The 20-Year-National Strategies has been used as the main directions of planning and evaluation. Furthermore, the guidelines for developing the administrative performance in in Local administrative organizations, Udon Thani province includes the long term plan, goal setting, index, the standard of performance, consulting, preparation, evaluation guidelines, administrative design with reporting, and the morale boosting of work performance.